Profile of chronic kidney disease related-mineral bone disorders in newly diagnosed advanced predialysis diabetic kidney disease patients: A hospital based cross-sectional study. (December 2017) - Ray, S.; Beatrice, A.M.; Ghosh, A.; Pramanik, S.; Bhattacharjee, R.; Ghosh, S.; Raychaudhury, A.; Mukhopadhyay, S.; Chowdhury, S.
Abstract: Aim: Chronic kidney disease related-mineral bone disorder (CKD-MBD) has been poorly studied in pre-dialysis Indian CKD population. There are limited data on the pattern of these disturbances in diabetic CKD patients. Therefore, a study was conducted to find out the profile of mineral bone disorders in T2DM patients with pre-dialysis CKD. Methods: In this cross-sectional design, diabetic patients with newly-diagnosed stage 4 and 5 CKD were evaluated. Serum levels of calcium, phosphorus, intact parathyroid hormone (iPTH), 25 hydroxy vitamin D and total alkaline phosphatase (ALP) were measured in all patients. Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (DXA). Results: A total of 72 eligible patients participated (44 males, 28 females; age 54.2 ± 11.7). Patients with CKD Stage 5 had a lower level of corrected serum calcium and significantly higher level of inorganic phosphorus, total ALP and iPTH as compared to stage 4 patients. Overall, 38.5% were hypocalcemic, 31.43% were hyperphosphatemic. 24.2% of CKD subjects were vitamin D deficient (<10 ng/ml) and 41.4% having vitamin D insufficiency (10–20 ng/ml). In stage 4, hyperparathyroidism (iPTH > 110 pg/ml) was detected in nearly 43% of patients. In stage 5, only 32% patients was found to have hyperparathyroidism (iPTH > 300 pg/ml). There was a good correlation between iPTH and total ALP (r = 0.5, p = 0.0001) in this cohort. 25 (OH) vitamin D was inversely correlated with ALP (r = −0.39, P = 0.001) and showed negative correlation with urine ACR (r = −0.37, P = 0.002). As a group, the osteoporotic CKD subjects exhibited higher iPTH (220.1 ± 153.8 vs. 119 ± 108 pg/ml, p < 0.05) as compared to those who were osteopenic or had normal bone density. There was significant correlation between BMD and iPTH (adjusted r = −0.436; P = 0.001). In the multivariate regression model, we found intact PTH to predict BMD even after adjustment of all the confounders. Conclusion: The current study showed that adynamic bone disease is prevalent even in pre-dialysis CKD population. High bone turnover disease may not be the most prevalent type in diabetic CKD. However, it could contribute to the development of osteoporosis in CKD subjects. Serum total ALP can serve as a biochemical marker to identify pattern of bone turnover where intact PTH is not available.